The Effect of Implementing the Team Games Tournament Learning Model Assisted by PowerPoint Media on the Learning Outcomes of PPKn Class VII at SMPN 11 Mataram - Herosita, Herosita; Ismail, M.; Basariah, Basariah; Haryanto, Edy (UNDIKMA, 2025)
The purpose of this study was to determine whether or not there was an effect of the application of the Team Games Tournament learning model assisted by PowerPoint media on the learning outcomes of class VII students in PPKn lessons. The research method used was a quantitative approach in the form of Nonequivalent Control Group Design. While the sampling used was Purposive Sampling and data collection used observation techniques and multiple choice tests. Based on the results of the data analysis, the average value of the pre-test results in the experimental class was 54.33 and in the control class it was 50.58. While the average value data for the post-test results in the experimental class was 82.66 and the control class was 76.16. So that the calculation of the t-test with the polled variance formula shows the results????ℎ????????????????????= 15,520 and????????????????????????= 2.0738. Thus????ℎ????????????????????>????????????????????????then Ha is accepted and Ho is rejected, which means that there is an influence of the Team Games Tournament learning model assisted by PowerPoint media on the learning outcomes of class VII students in PPKn lessons at SMPN 11 Mataram.